NILAI BUDAYA KEARIFAN LOKAL DALAM MELESTARIKAN LINGKUNGAN DI DESA CIMANGGU KECAMATAN NGAMPRAH BANDUNG BARAT - Sri Seti Indriani; Muhammad Zen Al-Faqih (Metacommunication: Journal of Communication Studies, 2020)
Humans as caliphs in the world must preserve the environment because human survival is very dependent on the environment. In encouraging the preservation of the environment, the community must live up to the values of wisdom that support the maintenance and preservation of the environment. However, in the digital age, this has led to a shift in cultural values of local wisdom. These values are increasingly fading because media exposure is increasingly dominating all human life. As experienced by the community in Cimanggu Village, Ngamprah District, West Bandung. They recognize that there are changes and shifts in cultural values. The focus of this research is to look at the cultural values  of local wisdom that exist in the village and how the meaning of the shift in cultural values  of local wisdom by the media for the local community. This research is qualitative research with a phenomenological study approach. Data collection techniques using observation, in-depth interviews, and documentation studies. The results of the study revealed that the cultural values  of local wisdom in the Cimanggu village were (1) Ngahiras, (2) Nyalin, (3) Tarawangsa, (4) Palak Science, (5) Palakiah, and (6) Kotok Jewer. The meaning of shifting the cultural values of local wisdom by the media for the local community includes: (1) Village communities perceive technological media as making rural communities more consumptive, (2) creating a shift in the professional direction of rice farmers into vegetable growers, and (3) Media exposure has a positive side as well as the negative side.